Auto-ignition of ionic liquid fuels with hydrogen peroxide triggered by copper-containing liquid promoter - Si-cheng Liao; Tian-lin Liu; Zhi-yu Zhou; Kang-cai Wang; Qing-hua Zhang (Energetic Materials Frontiers, 2024)
Research into next-generation propellants with green fuel–oxidizer pairs to replace the currently used highly toxic hydrazine–N2O4 system has attracted widespread attention. Ionic liquids (ILs) and hydrogen peroxide have demonstrated their feasibility as a green fuel and an oxidizer, respectively. However, the realisation of effective auto-ignition is the key problem. In this study, a new strategy to trigger the auto-ignition of ILs fuels with hydrogen peroxide by using a unique copper-containing liquid as the promoter is developed. The copper-containing promoter is designed such that its cationic structure is similar to that of the ILs fuels. Based on the principle of “like dissolves like,” the fuel and promoter can be miscible at any ratio to eventually form a catalytic fuel. In addition, the physicochemical properties (e.g. density, viscosity and decomposition temperature) and performance parameters (e.g. ignition delay time and specific impulse) of the as-prepared catalytic fuel are completely characterised. Owing to their excellent hypergolic performance with a short ignition delay time of 16 ms, in combination with the advantages of simple preparation, perfect solubility and green characteristics, the catalytic fuel–oxidizer pair demonstrates promise as bipropellants for rocket applications.